2020
DOI: 10.1021/acs.langmuir.0c00189
|View full text |Cite
|
Sign up to set email alerts
|

On the Behavior of Perfluorinated Persistent Organic Pollutants (POPs) at Environmentally Relevant Aqueous Interfaces: An Interplay of Hydrophobicity and Hydrogen Bonding

Abstract: The behavior of perfluorinated persistent organic pollutants (POPs), especially perfluoroalkyl carboxylic and sulfonic acids, at aqueous interfaces is crucial for their transport and speciation in the environment and subsequent immunotoxicity. Here, we investigate the surface prevalence and interfacial interaction of a prototype perfluorinated-POP, perfluoroheptanoic acid (PFHA), with environmentally relevant amphiphiles of varying hydrophobicity and head groups (C n H2n+1–X; n: 8 vs 16; −X: −OH vs −COOH) usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The variance of EF SSA in the submicron range could be further increased considering the different production mechanism of film droplets and jet droplets. For a mixture of surfactants, different compounds are thought to compete for surface area and the behavior of surfactant mixture is likely to be dominated by the component with the greatest surface activity. , Because of the higher surface-area-to-volume ratio of finer film droplets, there would be a relatively larger total surface area for PFAAs on the film cap to partition to during the droplets formation, which may explain the correlations between EF and 1/d 50 observed for compounds with NPC ≤ 9. However, the mechanism by which submicron film droplets are formed upon bubble bursting remains unclear .…”
Section: Discussionmentioning
confidence: 99%
“…The variance of EF SSA in the submicron range could be further increased considering the different production mechanism of film droplets and jet droplets. For a mixture of surfactants, different compounds are thought to compete for surface area and the behavior of surfactant mixture is likely to be dominated by the component with the greatest surface activity. , Because of the higher surface-area-to-volume ratio of finer film droplets, there would be a relatively larger total surface area for PFAAs on the film cap to partition to during the droplets formation, which may explain the correlations between EF and 1/d 50 observed for compounds with NPC ≤ 9. However, the mechanism by which submicron film droplets are formed upon bubble bursting remains unclear .…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this, the surface pressure of the DPPG monolayer/water interface (30 ± 2 mN/m) remains unchanged even after the addition of PFHA. In fact similar results were observed for PFHA at hexadecanol monolayer/water interface . We propose that anionic PFHA – is depleted from the protonated-DPPG interface because of repulsive interaction between their fluoroalkyl and alkyl chains.…”
Section: Resultsmentioning
confidence: 99%
“…However, surface tensiometry along with fluorescence anisotropy and differential scanning calorimetry have shown that an intermediate chain length PFCA (e.g., perfluorooctanoic acid (C8)) penetrates into DPPC bilayers. Using interface-selective vibrational spectroscopy, we have recently shown that the interaction of perfluoroheptanoic acid (PFHA) with conventional fatty acid and alcohol are governed by their relative hydrophobicity and headgroup-specific interaction . Therefore, the perturbation of different lipid monolayers by an intermediate chain length PFCA (∼ C8) may differ from those of the long chain PFCAs (∼ C12 or higher).…”
Section: Introductionmentioning
confidence: 97%
“…In an ER mechanism, one of the reactants of a bimolecular surface reaction reacts directly from the gas phase, which we suggest could be the gaseous electrons in the anode sheath of the plasma. These electrons can interact with the hydrophobic tail of PFOA, which protrudes upward and away from the water surface . The slight decrease in defluorination rates over time (Figure c) may be the result of transport limitations or the formation of shorter-chain PFAS, which have lower surface activity, thus lowering the surface concentration.…”
Section: Resultsmentioning
confidence: 99%